Logical Connectives Modulate Attention to Simulations Evoked by the Constituents They Link Together - Dumitru, Magda L.; Joergensen, Gitte H. (Frontiers in Psychology, 2018)
In previous studies investigating logical-connectives simulations, participants focused their attention on verifying truth-condition satisfaction for connective expressions describing visual stimuli (e.g., Dumitru 2014; Dumitru & Joergensen 2016). Here, we sought to replicate and extend the findings that conjunction and disjunction simulations are structured as one and two Gestalts respectively, by using language – picture matching tasks where participants focussed their attention exclusively on stimuli visuospatial properties. Three studies evaluated perceptual compatibility effects between visual displays varying stimuli direction, size, and orientation, and basic sentences featuring the logical connectives AND, OR, BUT, IF, ALTHOUGH, BECAUSE, and THEREFORE (e.g., “There is blue AND there is red”). Response times highlight a correlation between Gestalt arity in connective simulations and visual attention patterns, such that words referring to constituents in the same Gestalt were matched faster to visual stimuli displayed sequentially rather than alternatively, having the same size rather than different sizes, and being oriented along axes other than horizontal. The results also highlight attentional patterns orthogonal to Gestalt arity: visual stimuli corresponding to simulation constituents were processed faster when they appeared onscreen from left to right than from right to left, when they were emphasised or de-emphasised together (i.e., faster processing of all-small or all-large stimuli pairs), and when they formed a downwards-oriented diagonal, which signals a simulation boundary. More generally, our findings suggest that logical connectives rapidly evoke simulations that trigger top-down attention patterns over the grouping and properties of visual stimuli corresponding to the constituents they link together.